Keeping religious institutions secure - McLamb, Jennie-Leigh (Oxford UK ; Waltham, MA : Butterworth-Heinemann, an imprint of Elsevier, 2015)
Keeping Religious Institutions Secure explores the unique vulnerabilities that churches, synagogues, and mosques face in regards to security, making them attractive to criminals who see them as easy targets. The text illustrates why all places of worship should think about security and the types of breaches that can drive people away. The book focuses on the most frequent security concerns experienced by houses of worship, including embezzlement, vandalism, assault, hate crime, and in rare cases, an active shooter-and how to help prevent them from occurring. Beginning with an overview of the basic security concepts and principles that can enhance the security of any religious facility, it then delves deeply into the particular security concerns of houses of worship, including the use of volunteers, protecting religious leaders, ensuring safety for children and teens, interacting with local law enforcement, handling the media, and much more.
15 -- Implementing and Training.
Includes index.
Vendor-supplied metadata.
Elsevier
Keywords: Religious institutions -- Safety measures; Religious institutions -- Security measures; Crime -- Religious aspects; BODY, MIND & SPIRIT / Gaia & Earth Energies; RELIGION / Christianity / General; Church and state -- United States; Church and state; Religion; Electronic books